Change at last in auditing standards. (1st January 2013) - Sy, Aida; Tinker, Tony
Auditing and the standards are an on-going work as they deal with business which changes continually. Each time there is a major change in the business world, the standards must be updated or almost completely removed and replaced by new standards. This implies that there is a delay in setting the next standards; furthermore, this can harm business. This article is concerned with the auditing standards and their effects on business. The paper shows how the Public Company of Accounting Oversight Board and the Securities Exchange Commission are critical to the auditing standards settings.